Transcription factor KLF2 is associated with the dysfunctional status of NK cells and the prognosis of pediatric B-ALL patients - Wu, Fang; Xu, Huimin; Zhang, Benshan (Frontiers in Oncology, 2025)
BackgroundNatural killer cells, an important component of the innate immune system, can directly recognize and lyse virally infected or transformed cells. However, NK cells fail to restrain the growth of malignancies, such as B-cell acute lymphoblastic leukemia (B-ALL). The molecular genetics of NK cells in the B-ALL bone marrow microenvironment and the mechanisms underlying the inhibited function of NK cells at the single-cell level remain largely elusive.MethodsIn this study, we studied the frequency and absolute number of NK cells in peripheral blood samples collected from 43 healthy volunteers and 104 pediatric B-ALL patients diagnosed at Hunan Children’s Hospital. We also analyzed published single-cell RNA sequencing (scRNAseq) data from B-ALL and normal bone marrow samples using unsupervised clustering. Our findings were further validated using bulk transcriptomic data and clinical data from a cohort of 139 B-ALL bone marrow samples.ResultsWe found that the frequency and number of NK cells were significantly decreased in the bone marrow and peripheral blood of B-ALL patients. In-depth analysis of scRNAseq data identified 12 NK cell clusters. Among them, the C2 cluster, which is present in healthy bone marrow but reduced in B-ALL bone marrow, displays overexpression of a transcription factor KLF2 and a significant downregulation of the “leukocyte proliferation” pathway. Furthermore, we found that the expression of KLF2 in B-ALL at diagnosis was positively correlated with the percentage of leukemia cells and the positive rate of minimal residual disease (MRD), indicating that KLF2 is a marker of poor prognosis.ConclusionThere are dramatic differences at the single-cell level in the transcriptomics of NK cells between healthy donors and B-ALL patients. A transcription factor, KLF2, which is enriched in the C2 cluster of NK cells, has been suggested to regulate the proliferation of NK cells and is associated with poor prognosis of pediatric B-ALL.